TENUN KUBANG: SEMANGAT MEMPERTAHANKAN SENI TRADISI DARI PENGARUH MODERNITAS - Dini Yanuarmi; Widdiyanti Widdiyanti (Corak : Jurnal Seni Kriya, 2016)
This research is aimed at analysing the preservation and harmonisation Kubang weavinginto development of technology and modernisation. Tenunan Kubang (Kubang weaving) as atraditional art does not necessarily mean as a piece of cloth woven from threads with certaindesigns, colours, and motives, yet it also contain the socio-cultural values of the area where itoriginates and develops. As a traditional art, every cloth possesses splendidly woven motives.The motives are used to be seamlessly woven with some certain, seemingly-tough level ofdifficulty by using the manual-traditional weaving equipment. The influences of modernisationare considered as an effort to preserve a sustainable tradition of Kubang weaving art. TheApproaches in the analysis is emphasied on sociological aspects of Kubang weaving products.The data for the analysis are collected by using both the library research and field observation.The results indicated that the long run of the Kubang weaving had always been simultaneous tothe change and development of the ages. Under the circumstances, Kubang weaving appearedas a creative, innovative, and competitive product that maintained cultural and traditionalvalues. Without those values, Kubang weaving shall loose its identity and at the same time, shallbe meaningless and abandoned by the society.Keywords: Kubang Weaving, Traditional Art, Motives, Minangkabau